Design and evaluation of loop-mediated isothermal amplification for rapid detection of Enterocytozoon bieneusi - Fatemeh Mahdavi; Hamed Mirjalali; Maryam Niyyati; Seyyed Javad Seyyed Tabaei; Amir Shamloo; Hamid Asadzadeh Aghdaei (Food and Waterborne Parasitology, 2024)
Enterocytozoon bieneusi is one of the most prevalent microsporidia species, responsible for more than 90% of human and animal microsporidiosis. Microsporidia species, particularly E. bieneusi, are frequently reported from waterborne and foodborne outbreaks. Therefore, early detection is crucial in clinics and outbreak investigations. This study aimed to design a loop-mediated isothermal amplification (LAMP) for rapid detection of E. bieneusi. Total DNA was extracted from 30 E. bieneusi –positive samples, which had been confirmed with nested PCR. LAMP primers were designed based on the identical fragment of small subunit ribosomal RNA (SSU rRNA) gene. LAMP reactions were performed at 63 °C for 60 min. The sensitivity and specificity of the assay were analyzed and the results of amplification were compared to real-time PCR. Our results showed that the LAMP assay successfully amplified 25/30 (83.3%) samples. The specificity results indicated no false positive with other microorganisms. Furthermore, the LAMP method exhibited a sensitivity (limit of detection, LoD) as low as 34 ag/μL of total DNA. Compared to the LAMP assay, real-time PCR was able to detect all 30 nested PCR-positive samples. Our findings showed that the LAMP assay was able to detect 83.3% of E. bieneusi-positive samples. Although the current assay was not able to detect all nested PCR-positive samples, the lack of need for specific instruments, rapid processes, and high specificity makes LAMP assay a suitable tool for screening.